Research at the University of Western Australia on Structure Protections against Blast and Impact Loads - Hao, Hong; Ma, G. (Engineers Media, 2012)
One of the research focus areas of the Structural Engineering Group in the School of Civil and Resource Engineering at the University of Western Australia (UWA) is analysis and design of structures against blast and impact loads. Our research activities spread in a wide spectrum related to structure protections against blast and impact loads, including modelling shock wave propagation and prediction of blast loads on structures; quantification of dynamic material properties and development of dynamic material models; developing fibre-reinforced polymer (FRP) materials with new fibre types; development of theoretical and numerical approaches to predict blast fragmentation; numerical simulation, laboratory impact tests and field blast tests to quantify the effectiveness of FRP strengthening of reinforced concrete structures; and simulation of damage and progressive collapse of building and bridge structures to blast load. The research approaches include theoretical derivations, numerical simulations, and laboratory impact and field blasting tests. These researches are funded by a few ARC Discovery projects. Some of them are carried out with collaborations with researchers in other universities in Australia and other countries. This paper summarises a few research projects, and demonstrates the research capabilities related to protective structures in UWA.